Transfer of Ownership of Forests in the Western and Northern Teritories after World War II: Nationalization and Reprivatization - Jaroszyk-Pawlukiewicz, Joanna (Studia Historiae Oeconomicae, 2018)
The article concerns the transfer of ownership of forest property, nationalized after World War II. It covers the subject matter of the process of property acquisition by way of nationalization decrees, in particular in the area of the so-called Regained Territories and dilemmas related to the issue of reprivatization. The work includes issues proposed over the years and existing statutory solutions, as well as case law affecting the interpretation of legal norms.